Do international remittances promote poverty alleviation? Evidence from low- and middle-income countries - Prianto Budi Saptono; Gustofan Mahmud; Li-fen Lei (IZA Journal of Development and Migration, 2022)
Unlike previous empirical studies, this paper investigates the contemporaneous and lagged impacts of international remittances on poverty alleviation using data for 65 low- and- middle-income countries from 2002 to 2016. By using two-stage least square (2SLS) regression analysis, this study establishes that, in general, international remittances per gross domestic product (GDP) significantly mitigate poverty. On average, a 10-percentage-point increase in remittances will lead to a similar decrease in the poverty headcount ratio at USD 1.90 a day, a 4.8-percentage-point decline in poverty gap ratio at USD 1.90 a day, and a 6.7-percentage-point reduction in the poverty gap ratio at USD 3.20 a day. This result remains robust with the inclusion of political factors in the model. Moreover, the system-generalized method of moments (SGMM) estimations found that the contemporaneous effects of international remittances are much more substantial than their lagged effects. This indicates that most of the poverty alleviation role of remittances is contributed by its direct effect on increasing the wealth index of recipient households rather than the spillover effect on other members of the community. Therefore, we strongly suggest that efforts be made to improve the remittance infrastructures, especially in recipient countries, and the development of cooperatives in the enclaves of migrant workers to spread the beneficial effects of remittances to all members of society.
Keywords: F22; F24; I32; 330; international remittances; poverty; 2SLS; SGMM; low- and middle-income countries